Impact Of Classical Music Playing On Plant Growth - Fiky Maulana; Chairun Nisa; Muhammad Syapuwan Julham Nst; Shabrina Hanifati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Classical music has been a part of human culture for a long time, and its effects on human emotions and cognitive development have been documented. However, the impact of classical music on plant growth and development is relatively unknown. This paper examines the potential effects of classical music on plant growth, development, and behavior. Plants are known to respond to environmental stimuli, including light, temperature, and touch. However, the effect of music on plant growth and development is relatively unknown. Recent studies have shown that plants may be sensitive to sound waves, including music, and that exposure to certain frequencies and rhythms can affect plant growth and developments This paper hypothesizes that classical music has a positive impact on plant growth and development through influences on plant physiology and behavior.